2013
DOI: 10.1002/gps.3966
|View full text |Cite
|
Sign up to set email alerts
|

Blood pro‐inflammatory cytokines in Alzheimer's disease in relation to the use of acetylcholinesterase inhibitors

Abstract: Results from animal studies suggesting a modulatory anti-inflammatory role for AChEIs was not advanced in this study. In individuals with AD, very limited evidence currently exists to support the hypothesis that AChEIs may influence inflammatory blood markers and function beyond the enhancement of neuronal transmission. However, further studies assessing a wider range of inflammatory markers and processes are still needed before this hypothesis can be ruled out.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 37 publications
(52 reference statements)
1
11
0
Order By: Relevance
“…However, human studies in AD patients have not yet supported these findings; AChEI treatment was found to have no effect upon blood anti-oxidant (Klugman et al 2012) or pro-inflammatory biomarker levels after one year of treatment (Richardson et al 2013). …”
Section: Effect Of Treatmentmentioning
confidence: 93%
“…However, human studies in AD patients have not yet supported these findings; AChEI treatment was found to have no effect upon blood anti-oxidant (Klugman et al 2012) or pro-inflammatory biomarker levels after one year of treatment (Richardson et al 2013). …”
Section: Effect Of Treatmentmentioning
confidence: 93%
“…The HIV-1 coat glycoprotein gp120 has been reported to induce cellular injury and apoptosis in neurons upon sustained exposure both in vitro and in vivo , and is thought to contribute to the pathogenesis of HAND [4-9]. In addition to the surface glycoprotein CD4, gp120 also binds to the chemokine receptors CCR5 and CXCR4, which are expressed by neurons, astrocytes and microglia [7,10-12].…”
Section: Introductionmentioning
confidence: 99%
“…Acetylcholinesterase inhibitors and omega-3 fatty acids have not shown significant effects on IL-6 or TNF-α levels in the blood [56,57]. Conflicting data presented in studies of cytokine levels in AD may reflect different stages of disease and possible importance of CSF cytokine studies.…”
Section: Neurobehavioral Diseasementioning
confidence: 99%